Alpha reactivity to first names differs in subjects with high and low dream recall frequency - RUBY, Perrine M.; Blochet, Camille; Eichenlaub, Jean-Baptiste; Bertrand, Olivier; Morlet, Dominique; Bidet-Caulet, Aurélie (Frontiers in Psychology, 2013)
Studies in cognitive psychology showed that personality (openness to experience, thin boundaries, absorption), creativity, nocturnal awakenings, and attitude toward dreams are significantly related to dream recall frequency (DRF). These results suggest the possibility of neurophysiological trait differences between subjects with high and low DRF. To test this hypothesis we compared sleep characteristics and alpha reactivity to sounds in subjects with high and low DRF using polysomnographic recordings and electroencephalography (EEG). We acquired EEG from 21 channels in 36 healthy subjects while they were presented with a passive auditory oddball paradigm (frequent standard tones, rare deviant tones and very rare first names) during wakefulness and sleep (intensity, 50 dB above the subject’s hearing level). Subjects were selected as High-recallers (HR, DRF = 4.4 ± 1.1 dream recalls per week) and Low-recallers (LR, DRF = 0.25 ± 0.1) using a questionnaire and an interview on sleep and dream habits. Despite the disturbing setup, the subjects’ quality of sleep was generally preserved. First names induced a more sustained decrease in alpha activity in HR than in LR at Pz (1000-1200ms) during wakefulness, but no group difference was found in REM sleep. The current dominant hypothesis proposes that alpha rhythms would be involved in the active inhibition of the brain regions not involved in the ongoing brain operation. According to this hypothesis, a more sustained alpha decrease in HR would reflect a longer release of inhibition, suggesting a deeper processing of complex sounds than in LR during wakefulness. A possibility to explain the absence of group difference during sleep is that increase in alpha power in HR may have resulted in awakenings. Our results support this hypothesis since HR experienced more intra sleep wakefulness than LR (30 ± 4 vs 14 ± 4 min). As a whole our results support the hypothesis of neurophysiological trait differences in high and low-recallers